Human Resources Planning (HR) Business Face Care Products PT. Indo Bright Skincare - Nuraini Setiawati Suwarni; Tantri Yanuar Rahmat Syah; Semerdanta Pusaka; Dadan Ramdhani (Jurnal Mantik, 2021)
PT. Indo Bright Skincare is a company in the form of a limited liability company which is engaged in cosmetics, especially facial care products, which is located on Jl. Sheikh Nawawi, Matagara, Tigaraksa, Tangerang Regency, Banten, Indonesia with an area of 2000 square meters. PT. Indo Bright Skincare focuses on facial care products with black garlic ingredients that do not yet exist in Indonesia. The product uses the right formulation with ingredients that are safe for health and guaranteed to be halal. This study aims to describe human resource management, to analyze the internal and external business environment at PT. Indo Bright Skincare and to develop a business development plan on the human resource aspect. Researchers used qualitative descriptive methods to obtain the required data. From the results of the study it can be said that in running the business of PT. Indo Bright Skin Care. Human resource planning, including job analysis and design, human resource planning, recruitment, training and HR development. compensation, social security, job evaluation, performance bonuses, and termination of employment. The Human Resources (HR) budget designed by PT. Indo Bright Skincare pays attention to the rules set by the government by taking into account allowances, work accidents, pensions, health and THR. In the first year the number of employees was 14 people.